Coupling effects of preheating time and extraction medium pH on red radish anthocyanin yield, glucosinolate degradation and off‐odour removal. (1st November 2017) - Chen, Wentian; Karangwa, Eric; Yu, Jingyang; Duhoranimana, Emmanuel; Xia, Shuqin; Feng, Biao; Zhang, Xiaoming; Jia, Chensheng
Summary: In this study, the effect of combined preheating time (2, 5, and 10 min) and extraction medium pH (2.5, 3.5, and 4.5) on total monomeric anthocyanin yield, and removal of off‐odour in red radish anthocyanins were evaluated. The tentative anthocyanin identification showed twelve pelargonidin anthocyanins, and only nine were identified in samples preheated for 10 min. Sample preheated for 10 min and extracted at pH 4.5 showed lower the anthocyanin yield (98.02 mg/100 g, FW), lighter colour and higher percentage polymeric colour compared with that preheated for 2 min and extracted at pH 2.5. However, prolonged preheating time (10 min) significantly reduced myrosinase enzyme activity by 73%. Additionally, results showed that preheating time and extraction medium pH have negative and significant effect on the total monomeric anthocyanin yield, while they showed positive and negative significant effect on the total glucosinolate degradation. Furthermore, the sensory evaluation results revealed no significant difference in radish odour for samples preheated for 2 and 5 min followed by anthocyanin extraction in pH 2.5 medium. It might therefore be concluded that the combination of moderated preheating treatment time (≤5 min) and lower extraction medium pH could be effective to reduce the off‐odour characteristics and maintaining high yield and stable red radish pigment. Abstract : Effects of preheating time and extraction medium pH on red radish anthocyanin yield, glucosinolate degradation and off‐odour removal.